Peacebuilding Efforts in Civil War-Affected Countries in Afghanistan - Ahmadzai, Ibrahim (Journal of Conflict Management, 2024)
Purpose: The aim of the study was to analyze peacebuilding efforts in civil war-affected countries in Afghanistan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Peacebuilding in war-torn Afghanistan faces hurdles due to ongoing conflict, ethnic divides, and Taliban resurgence. Governance reforms and reconciliation efforts struggle amidst poverty and corruption. Despite some progress, achieving lasting peace is an uphill battle. Unique Contribution to Theory, Practice and Policy: Liberal peacebuilding theory, critical peacebuilding theory & relational peacebuilding theory may be used to anchor future studies on the peacebuilding efforts in civil war-affected countries in Afghanistan. Peacebuilding efforts should prioritize local ownership, inclusivity, and participatory approaches that empower affected communities to take an active role in shaping their own futures. Peacebuilding efforts should be integrated into broader development, security, and governance frameworks to ensure coherence, coordination, and sustainability.